On multivalent receptor activity of GM1 in cholesterol containing membranes - Šachl, Radek; Amaro, Mariana; Aydogan, Gokcan; Koukalová, Alena; Mikhalyov, Ilya I; Boldyrev, Ivan A; Humpolíčková, Jana; Hof, Martin (Biochimica et biophysica acta, 2015)
Gangliosides located at the outer leaflet of plasma membrane are molecules that either participate in recognizing of exogenous ligand molecules or exhibit their own receptor activity, which are both essential phenomena for cell communication and signaling as well as for virus and toxin entry. Regulatory mechanisms of lipid-mediated recognition are primarily subjected to the physical status of the membrane in close vicinity of the receptor. Concerning the multivalent receptor activity of the ganglioside GM1, several regulatory strategies dealing with GM1 clustering and cholesterol involvement have been proposed. So far however, merely the isolated issues were addressed and no interplay between them investigated. In this work, several advanced fluorescence techniques such as Z-scan fluorescence correlation spectroscopy, Förster resonance energy transfer combined with Monte Carlo simulations, and a newly developed fluorescence antibunching assay were employed to give a more complex portrait of clustering and cholesterol involvement in multivalent ligand recognition of GM1. Our results indicate that membrane properties have an impact on a fraction of GM1 molecules that is not available for the ligand binding. While at low GM1 densities (~1 %) it is the cholesterol that turns GM1 headgroups invisible, at higher GM1 level (~4 %) it is purely the local density of GM1 molecules that inhibits the recognition. At medium GM1 content, cooperation of the two phenomena occurs. This article is part of a Special Issue entitled: Nanoscale membrane organisation and signalling.
Keywords: Cluster Analysis; Hydrazines; ligandy; Cholera toxin; G(M1) Ganglioside; titrace; Diffusion; Computer Simulation; Cholesterol; Fluorescence Resonance Energy Transfer; Ligands; Gangliosides; shluková analýza; difuze; Antibunching; ovce; Sheep; receptory buněčného povrchu; Cell Membrane; cholesterol; Animals; hydraziny; Monte Carlo Method; G(M1) gangliosid; zvířata; metoda Monte Carlo; buněčná membrána; rezonanční přenos fluorescenční energie; Receptors, Cell Surface; počítačová simulace; Energy transfer; Titrimetry; Fluorescence correlation spectroscopy